Predictive modelling of social capital among library workers: a machine learning approach - Wojciechowska, Maja; Topolski, Mariusz (Malaysian Journal of Library and Information Science, 2024)
Social capital is an important asset for the development of communities, including communities linked to specific types of libraries. Despite numerous studies, no models dedicated to measuring this specific area have been developed yet. The paper proposes a model predicting the level of social capital among library workers with the use of machine learning methods. Its purpose is to identify the attributes that determine the level of social capital in a given community in order to enable the development of key areas. The model may be adapted for use in other groups, e.g. among library users or library non-users, in order to analyse social capital in the entire local community.